Seasonal influenza vaccine uptake among Chinese in Hong Kong: barriers, enablers and vaccination rates - Kai Sing Sun; Tai Pong Lam; Kit Wing Kwok; Kwok Fai Lam; Dan Wu; Pak Leung Ho (Taylor & Francis Group, 2020)
Background Low influenza vaccination rates were observed in Asian countries including China. This study investigated the updated seasonal influenza vaccination rates among Chinese in Hong Kong, and the barriers and enablers to vaccination. Methods Eight focus groups were conducted among the Chinese general public, followed by a telephone survey between March and April 2018 with 2,452 respondents (response rate 41.4%). Results Of the survey respondents, 29.1% had received influenza vaccine in the past 12 months. A majority of them agreed with 'enhancing immunity' (94.4%) and 'feeling safer' (92.3%) as their reasons for vaccination, followed by the belief on 'quicker recovery' if they had influenza (69.5%), and free/subsidized vaccine (53.8%). Among respondents who had not received influenza vaccine, 71.2% 'believed in the strength of their own immunity' and 65.6% perceived 'low-risk of getting influenza'. Less than half were 'worried about side-effects' and 'effectiveness'. The groups aged 65-74 and 75 or above had vaccination rates of 49.1% and 69.9%, respectively, in contrast to 13.9% for the group aged 18-64. A rate of 37.9% for children was reported by the 442 respondents having children. Conclusions The high uptake of vaccines among the children and elderly suggests the positive impact of the subsidy and outreach programs. However, young and middle-aged adults tend to believe in the strength of their own immunity and underestimate the infection risk. Public education should emphasize that inactivated vaccines such as influenza vaccines work by means of the viral antigens stimulating the host's immune system toward the major types of seasonal influenza.